Analysis of Operating Conditions Pertaining to 3-Phase 4-Way Power Networks Using Statistical Method for Load Calculation - A. G. Arutiounian (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper proposes a methodology for an analysis of phase-like load distribution and calculation of an optimum number of single electrical receivers per every phase of 3-phase 4-way power networks of 0.4/0.23 kV where a statistical method is used for calculation of electric loads.  An index is suggested for evaluation of operational electric load uniformity by phases. The paper contains an analysis of concrete examples of electric load diagrams according to the considered methodology.